Alicia : a Clique novel - Harrison, Lisi. (New York : Little, Brown and Co., 2008)
When Alicia goes back to Spain, she find that Europe's latest pop sensation is looking for a true Spanish beauty to star in his new video. Can she beat her cousins to win the role?
"Poppy."
Keywords: Cliques (Sociology) -- Fiction; Beauty, Personal -- Fiction; Beauty contests -- Fiction; Competition (Psychology) -- Fiction; Self-esteem -- Fiction; Conduct of life -- Fiction; Spain -- Fiction